A review on RNAi therapy for NSCLC: Opportunities and challenges. (10th November 2020) - Kumar, Vignesh; Yadavilli, Sairam; Kannan, Raghuraman
Abstract: Non‐small cell lung cancer (NSCLC) is the primary cause of cancer death worldwide. Despite developments in chemotherapy and targeted therapies, the 5‐year survival rate has remained at approximately 16% for the last four decades. NSCLC is a heterogeneous group of tumors that, through mutations and drivers, also demonstrate intra‐tumor heterogeneity. Thus, current treatment approaches revolve around targeting these oncogenes, often using small molecule inhibitors and chemotherapeutics. However, the efficacy of these therapies has been crippled by acquired and inherent drug‐resistance in the tumor, accompanied by increased therapeutic dosages and subsequent devastating off‐target effects for patients. Evidently, there is a critical need for developing treatment methodologies more effective than the current standard of care. Fortunately, RNA interference, particularly small interfering RNA (siRNA), presents an alternative of silencing specific oncogenes to control tumor growth. Although siRNA therapy is subject to rapid degradation and poor internalization in vivo, nanoparticles can serve as nontoxic and efficient delivery vehicles, even introducing combinational delivery of multiple therapeutic agents. Indeed, siRNA‐nanoconstructs possess extraordinary potential as an innovative modality to address clinical needs. This state‐of‐the‐art review summarizes the recent advancements in the development of novel nanosystems for delivering siRNA to NSCLC tumors and analyzes the efficacy of representative examples. By illuminating the most promising biomarkers for silencing, we hope to streamline current therapeutic efforts and highlight powerful translational opportunities to combat NSCLC. This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Biology‐Inspired Nanomaterials > Lipid‐Based Structures Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Nanoparticles serve as ideal vehicles to deliver siRNA molecules to NSCLC and suppress the oncogene of interest to sensitize to therapeutics.